Subject marking in Awing - Henry Zamchang Fominyam (LibraryPress@UF, 2021)
This paper investigates the principles that govern subject marking in Awing (Grassfields Bantu). We observe that the subject marker (SM) that doubles the subject is sometimes obligatory, sometimes optional and sometimes prohibited. We argue that it is the referentiality of the subject that controls the distribution of the SM in Awing, rather than factors such as its morpho-syntactic features or its information structural status, which have been identified to govern argument doubling in a number of other languages with a similar phenomenon. The empirical evidence leads us to conclude that the SM is a pronominal element in Awing rather than an agreement marker. When it occurs, it functions as the argument of the verb and the associated subject NP is base-generated in the left periphery of the clause; when it is absent, the NP is the verbal argument. Awing thus qualifies as a pronominal argument language in the sense of Jelinek (1984); Bresnan and Mchombo (1987); Baker (1996).